Cardiac Biomarker for Acute Cardiac Toxicity in Breast cancer Patient Receiving Anthracycline or Trastuzumab in King Abdulaziz University Hospital, Observation Study - Shadi Alkhayyat (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine if using cardiac biomarker will predict cardiotoxicity in patients with breast cancer receiving cardiotoxic anti-cancer therapy. Chemotherapy, biological therapy and immunotherapy are associated with this type of toxicity. In our study we focused on the use of anthracycline and trastuzumab. Methods: We conducted an observational study in which we followed patients who received cardiotoxic medication and assessed cardiac biomarker before therapy, 48-72 hours after and before next cycle. A mixed effect linear regression model was used with patient as a random intercept to model the clinical endpoints before and after the chemotherapy while controlling important demographics Results: 30 patients with early breast cancer who are receiving treatment at King Abdulaziz University Hospital were eligible. Two patients developed drop in left ventricular ejection fraction. No patient developed symptoms of congestive heart failure. There was no correlation between the elevation in cardiac markers and the decrease in the ejection fraction. Conclusion: In a small observational study on breast cancer patients at KAUH, there was no correlation between cardiac markers changes and reduction in the left ventricular ejection fraction. A larger cohort will be of benefit to prove if there is a significant correlation.